Sejarah dan Perkembangan Masjid Al-Mashun Medan Sebagai Warisan Kesultanan Deli - Silaen, Anggraini; Sagala, David Saputra Woffelson; Mahyuni, Ika Purnamasari Masdaliva; Simbolon, Raul Gokmauli Alfredo; Purba, Yolanda Ezerin (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to trace the history of Al-Mashun Grand Mosque, which is known as the heritage of the Sultanate of Deli. Al-Mashun Grand Mosque was established in 1906, and completed in 1909. The entire cost of building the mosque was borne by Sultan Maamun Al-Rasyid Perkasa Alamsjah IX who was the Sultan at that time. Al-Mashun Grand Mosque became the pride of the Muslim community in Medan at that time because the mosque was very magnificent in its time. Research on Al-Mashun Grand Mosque: A Study of Socio-religious History is relevant using qualitative research because it fulfils the characteristics of qualitative research, especially in terms of in-depth data disclosure through interviews, observations and document reviews of what informants do, how they carry out activities, what activities are carried out for and why they do virtue or goodness (good morals) in real reality.